The football association injury and illness surveillance study: the incidence, burden and severity of injuries and illness in men's and women's international football - Sprouse, B.; Alty, J.; Kemp, S.; Cowie, C.; Mehta, R.; Tang, A.; Morris, J.; Cooper, S.; Varley, I. (Sports Medicine, 2024)
Objectives: To determine the incidence and characteristics of injury and illness in English men`s and women`s senior and youth international football. Methods: Time-loss injuries and illnesses, alongside match and training exposure, were collected across 8 seasons (2012-2020) in youth (U15, U16, U17, U18, U19) and senior (U20, U21, U23, senior) English men`s and women`s international teams. Analysis of incidence, burden, and severity of injury and illness was completed. Sex-specific comparisons were made between the senior and youth groups, and across the 8 seasons of data collection. Results: In men`s international football, 535 injuries were recorded (216 senior; 319 youth) during 73,326 h of exposure. Overall, match injury incidence (31.1 ± 10.8 injuries/1000 h) and burden (454.0 ± 195.9 d absent/1000 h) were greater than training injury incidence (4.0 ± 1.0 injuries/1000 h) and burden (51.0 ± 21.8 d absent/1000 h) (both P < 0.001). In women`s international football, 503 injuries were recorded (senior: 177; youth: 326) during 80,766 h of exposure and match injury incidence (27.6 ± 11.3 injuries/1000 h) and burden (506.7 ± 350.2 days absent/1000 h) were greater than training injury incidence (5.1 ± 1.8 injuries/1000 h) and burden (87.6 ± 32.8 days absent/1000 h) (both P < 0.001). In women`s international football, a group × season interaction was observed for training injury incidence (P = 0.021), with the senior group recording a greater training injury incidence during the 2015-2016 season compared to the youth group (14.4 vs 5.7 injuries/1000 h; P = 0.022). There was no difference in injury severity between match and training for men`s (P = 0.965) and women`s (P = 0.064) international football. Conclusions: The findings provide a comprehensive examination of injury and illness in English men`s and women`s senior and youth international football. Practitioners will be able to benchmark their team`s injury and illness incidence and characteristics to the match-play and training information provided in the present study.